Policy Capacity for Climate Change in Canada's Transportation Sector. Issue 1 (9th January 2013) - Newman, Joshua; Perl, Anthony; Wellstead, Adam; McNutt, Kathleen
Abstract When pursuing change, legacies of policy goals and instruments from an established paradigm often present constraints on fully embracing a newer paradigm, resulting in the layering of new policy goals and instruments on top of the existing base. In this article, we investigate the effect of layered paradigms on policy capacity at three different levels of policy making in the Canadian transportation sector. Using analysis of government publications and budget data, virtual policy network analysis, quantitative analysis of data from a survey of Canadian policy analysts, and direct interviews with policy managers in two provinces, we demonstrate how this layering of legacy goals (and consequent policy incapacity) is occurring at the macro, meso, and micro levels of policy making. We conclude that the layering of a new policy paradigm for climate change on top of the established paradigm for transportation development constrains policy capacity in this subsystem.